Acousto-optical properties of metamaterials. (February 2016) - Pustovoit, V.I.
Abstract: The possibility of the effective use of metamaterials in acousto-optics is demonstrated. It is shown that photoelastic constants that determine a change in the dielectric constant of a heterogeneous medium under the action of a sound wave can significantly exceed the corresponding constants for conventional crystals. We have analysed the mechanisms of the dielectric constant variation in a heterogeneous medium consisting of nanoparticles in the form of ellipsoids and have found explicitly the values of the photoelastic constants. It is shown that the mechanism of the dielectric constant variation in a longitudinal sound wave is reduced to a change in the local concentration of nanoparticles in the bulk and in a transverse acoustic wave – to a local rotation of space-oriented nanoellipsoids. It is also shown that the use of metamedia with a nonuniform distribution of nanoparticles provides a unique opportunity for designing qualitatively new instruments and devices that cannot be produced on the basis of conventional crystals. It is noted that metamaterials open ample opportunities for creating devices of the IR region of the spectrum due to the absence of restrictions on the size of such media.